ETV4/ALYREF-mediated glycolytic metabolism through PKM2 enhances resistance to ferroptosis and promotes the development of intrahepatic cholangiocarcinoma - Xiaohui Wang; Wenbin Duan; Zhongzhi Ma; Haoquan Wen; Xianhai Mao; Changjun Liu (Cancer & Metabolism)
Abstract Background Intrahepatic cholangiocarcinoma (ICC) is the second most common primary hepatocellular cancer. This study investigated whether ETV4, ALYREF, and PKM2 affect glycolytic metabolism and ferroptosis, thereby potentially influencing ICC. Methods Bioinformatic analysis was used to explore the expression levels and prognosis of ETV4, ALYREF, and PKM2 in ICC and their regulatory relationships were confirmed using in vitro experiments. Glycolytic metabolism and ferroptosis were examined, and chromatin immunoprecipitation and RNA immunoprecipitation experiments were performed to verify whether the ETV4, PKM2, and ALYREF could bind. The effect of ETV4/ALYREF on ICC was further confirmed by in vivo experiments. Results ETV4, ALYREF, and PKM2 were highly expressed in ICC. Overexpressed (oe)-ETV4 and oe-PKM2 promoted cell migration and increased glucose (GLU) utilization and lactate and intracellular adenosine triphosphate (ATP) production. Addition of the ferroptosis inducer Erastin to the above groups revealed that sh-ETV4 and sh-ALYREF increased lipid reactive oxygen species (ROS), malondialdehyde (MDA), and Fe2+ levels, and oe-PKM2 reversed these effects in the sh-ETV4 and sh-ALYREF groups. Oe-ETV4 promoted the expression of PKM2, whereas sh-ALYREF inhibited the same. ETV4 could bind to ALYREF and PKM2 promoter, and ALYREF could promote the stability of PKM2 in an m5C-dependent manner. In vivo, ETV4 promotes tumor growth and the expression of proteins related to glycolytic metabolism by regulating ALYREF. Conclusion ETV4 promotes ICC development and ferroptosis resistance by facilitating glycolytic metabolism, and regulating PKM2 transcription by directly binding to the PKM2 promoter. Additionally, it mediates m5C-dependent PKM2 stabilization by directly binding to ALYREF. This study identified a new potential therapeutic target for ICC.